Evolution of breast reconstruction in a tertiary care hospital in Mexico - Platas Galván, Santos Enrique; Chang, Emiliano O.; Anda, Melissa De; Torres, Raymundo (International Journal of Research in Medical Sciences, 2025)
Background: This study was performed to analyze the trends in breast reconstruction techniques over time, focusing on their evolution and comparing them with findings from previous studies. Methods: This retrospective study analyzed breast reconstruction procedures performed at the Plastic Surgery Department of the General Hospital of Mexico from January 2019 to December 2023. A total of 105 patients were included, focusing on patient demographics, procedure types, common histological subtypes, observed complications and trends in reconstruction techniques within the hospital and nationally. Results: The study included 105 patients with a mean age of 49 years, the 41–50 age group being the most prevalent (38.1%). A total of 105 reconstructive procedures were performed: latissimus dorsi flap in 69 patients (65.7%), TRAM flap in 21 patients (20%) and DIEP flap in 7 patients (6.7%). For alloplastic reconstructions, tissue expanders were used in 38 cases (36.2%) and implants in 36 cases (34.3%). Most patients (81.9%) had no complications; necrosis was the most common complication (6.7%). Radiotherapy was administered to 43 patients (41%), while 68 patients (64.8%) underwent chemotherapy. The most common oncological cause was ductal carcinoma (65.7%). Conclusions: Breast reconstruction at the General Hospital of Mexico has evolved toward safer and more effective procedures, tailored to the specific needs of each patient. The use of alloplastic methods and latissimus dorsi flaps predominates, reflecting global trends in breast reconstruction and highlighting progress in local surgical practices.